PENGELOLAAN OBJEK WISATA SEJARAH KERAJAAN SIAK DI KABUPATEN SIAK - Kusharyadi, Jeffry; Siddiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Siak as a growing area, and has always been in the campaigning slogan by Siak Regent Drs. H. Syamsuar, M.Si namely "Siak The Truly Malay" or Siak indeed wither area. Siak has a myriad of attractions that can be enjoyed by the community, both domestically and abroad, namely historical tourism, cultural tourism, culinary tourism, nature tourism and agrotourism. In realizing the slogan "Siak The Truly Malay" Siak Regency presents various panoramic underlying siak district as an area known as the Malay region. One of them is the number of heritage - historical remains a silent witness and proof that the district is indeed melayu area.Under these conditions, formulated the problem of how the Object Management History Siak Kingdom as well as the factors that meghambat in the management of historical attractions in Siak. This study uses the theory of Natural Luther Gulick in 2004 to find out how the planning, organization, coordination, budgeting, and oversight in the management of attraction Siak royal history. Qualitative research with descriptive method. Researchers are trying to reveal the facts in accordance with the reality. This study did not look for or explain the relationship, not test hypotheses or make predictions. Data will be explained by what so we get an understanding.Based on the results of research and discussion, it can be concluded that the management of historical attractions in the category Kingdom of Siak still not optimal. Lack of good planning, organization, coordination, budgeting and supervision make the management has not run optimally. The lack of knowledge and curiosity of employees regarding the management of historical attractions and other aspects related to the management of historical attractions making them incapable in preparing and planning for management of historical attractions. Lack of supervision and evaluation conducted by the Office of the performance and duties of the employees that make the employees do not feel responsible for the management of historical attractions.Keyword: Management, History